Sevo?urane Anaesthesia and Propofol Based Anaesthesia- A Comparative Study - Imran Nazir; Masarat Ara; Tufail Ahmad Sheikh (Academia Anesthesiologica International, 2021)
Background: Total intravenous anaesthesia (TIVA) is a technique of anaesthesia which involves use of intravenous drugs to anaesthetize the patient without the use of inhalational agents. The present study was conducted to compare sevoflurane (inhalational) anaesthesia and propofol (Tiva) based anaesthesia. Subjects and Methods : 80 ASA I and II patients, aged 18-65 years of either sex undergoing surgery under general anaesthesia were randomly divided into two groups. Group I received sevoflurane inhalational induction via a vital capacity rapid inhalational induction (VCRII) technique using 8% sevoflurane. Group II patients were induced with propofol i.v 2-2.5mg/kg. Parameters such as MAP and recovery profile was recorded in both groups. Results: Group I comprised of 22 males and 18 females and group II had 16 males and 24 females. The mean MAP (mmHg) in group I and II was 100.5 and 102.1, before induction was 98.2 and 97.7, after induction was 89.0 and 88.4, 5 minutes after intubation was 93.4 and 91.0, at 15 minutes was 100.1 and 97.8, at 30 minutes was 100.0 and 99.3 and at 45 minutes was 100.9 and 99.1 respectively. The recovery profile such as time of spontaneous eye opening was 9.5 minutes in group I and 13.2 minutes in group II, time to verbal communication was11.5 minutes in group I and14.3 minutes in group II and time to mental orientation was 15.6 minutes in group I and19.0 minutes in group II. The difference was significant (P< 0.05). Conclusion: Sevoflurane is better than propofol in terms of faster induction and rapid recovery.